If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x + 2(x + -2) = 60 Reorder the terms: x + 2(-2 + x) = 60 x + (-2 * 2 + x * 2) = 60 x + (-4 + 2x) = 60 Reorder the terms: -4 + x + 2x = 60 Combine like terms: x + 2x = 3x -4 + 3x = 60 Solving -4 + 3x = 60 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '4' to each side of the equation. -4 + 4 + 3x = 60 + 4 Combine like terms: -4 + 4 = 0 0 + 3x = 60 + 4 3x = 60 + 4 Combine like terms: 60 + 4 = 64 3x = 64 Divide each side by '3'. x = 21.33333333 Simplifying x = 21.33333333
| 4x+x-3=93 | | 15+35=-5(3x-10) | | 30-10x=5(2p-6) | | a^3-5a^2-16a+80=0 | | 45*2y=45 | | 4(6+3.2w)+7=60.2 | | 2(1)+1-3(1)+4= | | -12t+12t+-t+-11=3 | | 5(p-8)=-36+5p | | A(n)=2+(4-1)(-2.5) | | X+2x+x=32 | | 2(3x+6)=-36+30 | | h-h+h=7 | | 4t-t=18 | | 8(x-0.25)=4(2x-0.5) | | 5/34*17/20= | | 2q-5q+-9q=12 | | 5x-3=93 | | 0.20x+0.45(30)=25.5 | | 8-(3n-6)=9-4n | | (x-2)(x+1)=3 | | 11-2x=5(x+1)-7x | | t^6+6t^3-27=0 | | 9r+3=37r+7 | | 3(3+c)=2(c-7) | | k-2k+-7k=-18 | | 5x+21+3x=29 | | 10-2r=28 | | 3(n+1)-(7n-5)=-5n | | 2.33=(x-78)/3 | | 4+8=6+g | | a-18=7a |